The Weight Reduction of Charged Capacitors, Charge-Mass Interaction, and Einstein’s Unification - Lo, C. Y. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The Biefeld-Brown (B-B) effect consists of two parts: 1) the initial thrust is due to the electric potential that moves the electrons to the positive post; and 2) the subsequent lift is due to the separate concentration of the positive and the negative charges. The weight reduction of a charged capacitor is due to a repulsive charge-mass interaction, which is normally cancelled by the attractive current-mass interaction. In a charged capacitor, some electrons initially moving in the orbits become statically concentrated and thus a net repulsive force is exhibited. Based on observations, it is concluded that a repulsive charge-mass interaction is proportional to the charge density square and diminishes faster than the attractive gravitational force, and that the current-mass force is perpendicular to the current. This charge-mass interaction is crucial to establish the unification of electromagnetism and gravitation. To confirm general relativity further, experimental verification of the details of this mass-charge repulsive force is recommended. Moreover, general relativity implies that the photons must include gravitational energy and this explains that experiments show that the photonic energy is equivalent to mass although the electromagnetic energy-stress tensor is traceless. In general relativity,it is crucial to understandnon-linear mathematics and that the Einstein equation has no bounded dynamic solutions. However, due to following Einstein’s errors, theorists failed in understanding these and ignored experimental facts on repulsive gravitation. Since the charge-mass interaction occurs in many areas of physics, Einstein’s unification is potentially another revolution in physics. Moreover, the existence of a repulsive gravitation implies the necessity of re-justifying anew the speculation of black holes.